Development of Web-Based Leave Management System for Telkom Delivery Department Crowdsource Employees in PT Sigma Cipta Caraka - Sarungu, Cornelius Mellino; Baharizki, Frida; Kamila, Hana; Sugiharto, Via Alviola (Universitas Multimedia Nusantara, 2023)
Technology is one of the solutions that can bring automation to a process, with technology all processes can be more time efficient. This is necessary for some processes that were previously done manually. One of them is in Telkom Delivery’s division at PT Sigma Cipta Caraka, a company that has some crowdsource employees, who have the right to take leave every year. The current system can still be used because it still sends leave application messages using e-mail, this also indicates that it is not integrated properly. The purpose of designing this leave application information system is to provide a solution to the problem of managing employee leave so that it can run more efficiently. The methods used in the data collection process to obtain user requirements are observation, interviews, and literature study. To support the development of this information system, the author uses several technologies, namely the Laravel framework and MySQL database using certain software development lifecycle (SDLC). This research results in a leave management web application for crowdsource employees in PT Sigma Cipta Caraka.